Application of n-dodecane as an oxygen vector to enhance the activity of fumarase in recombinant Escherichia coli: role of intracellular microenvironment - Zhang,Sen (2018)
Abstract The effect of the intracellular microenvironment in the presence of an oxygen vector during expression of a fusion protein in Escherichia coli was studied. Three organic solutions at different concentration were chosen as oxygen vectors for fumarase expression. The addition of n-dodecane did not induce a significant change in the expression of fumarase, while the activity of fumarase increased significantly to 124% at 2.5% n-dodecane added after 9 h induction. The concentration of ATP increased sharply during the first 6 h of induction, to a value 7600% higher than that in the absence of an oxygen-vector. NAD/NADH and NADP/NADPH ratios were positively correlated with fumarase activity. n-Dodecane can be used to increase the concentration of ATP and change the energy metabolic pathway, providing sufficient energy for fumarase folding.